Tumor Angiogenesis and Modulators - Xu, Ke (IntechOpen, 2022)
Tumor angiogenesis is critical for tumor growth and progression. It is a multistep and complicated process, and the mechanism underlying tumor angiogenesis is not fully elucidated. Recent advances in tumor angiogenesis research have led to improved diagnosis, drug treatment, and clinical management of cancer. However, novel strategies for cancer treatment are urgently needed, especially biomarker discovery for diagnosis, prognosis, and targeted therapy. This book presents the most recent advances in tumor angiogenesis.